Pemberdayaan Masyarakat dalam Perintisan Destinasi Wisata Minat Khusus di Desa Hutan Jabranti, Kuningan - Windayani, Silma; Mandurroh, Resti Sri; Maulida, Alwi Zulfa; Fauzian, Mardiatul; Nugraha, Amalia; Pangestu, Aistu Nur Cahya; Friana, Danda; Richard, Fahri Syach; Hidayat, Farhan; Jaya, Genta Adha; Anjani, Lidia Tamia; Ibrahim, Maulana; Akbar, Muhamad Fathoni; Hamdani, Muhammad Habib; Bain, Unan Nur; Hendrayana, Yayan (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2024)
Jabranti Village, located in Kuningan Regency, is the focus of the Student Organization Capacity Strengthening Program (PPK Ormawa) for Nature Lovers Forestry Students (MAHAKUPALA) with the topic Forest Village. This area is rich in biodiversity, including the presence of flora, various fauna as well as local wisdom and the existence of cultural sites. The aim of this activity is to increase the use of local wisdom and natural resources by the community, create new groups, increase community competence in resource management, and form special interest educational tourism destinations based on environmental preservation and local culture. The method of implementing activities is providing outreach, biodiversity inventory, interviews, training and mentoring to local communities and special interest educational tourism management groups as well as non-timber forest product management groups. This series of activities received a good response from participants, providing a very significant increase, creating a new source of income and making Jabranti Village a center for forest conservation in Kuningan Regency.